An Evaluation of the Vietnamese Translated Version of “The Call of the Wild” by Nguyen Cung Ai and Vu Tuan Phuong . M.A Thesis Linguisti - Nguyễn, Thị Thu Hiền (University of Languages and International Studies, 2017)
It is undeniable that the assessment of translation is becoming of great important and receiving great concerns of many researchers. The more translations are published, the more necessary it is to control the quality of such works so that the readers can (...)